Factors influencing stone-free rate of Extracorporeal Shock Wave Lithotripsy (ESWL); a cohort study. (4th May 2022) - Wagenius, Magnus; Oddason, Karl; Utter, Maria; Popiolek, Marcin; Forsvall, Andreas; Lundström, Karl-Johan; Linder, Adam
Abstract: Objective: To evaluate the success rate of Extracorporeal Shock Wave Lithotripsy (ESWL) therapy and identify relevant treatment-specific factors affecting stone-free rate (SFR) after ESWL. Materials and methods: All ESWL treatments in the years 2016–2019, in Ängelholm Hospital, Skåne, Sweden were analysed retrospectively. Primary outcome was stone-free rate (SFR) at 3 months. Univariate logistic regression was used followed by multivariable regression. Lasso analysis was made to adjust for treatment-specific factors such as age, stone size, skin-to-stone distance (SSD), stone attenuation, number of treatments, stone location and presence of a urinary stent. Results: Factors affecting successful ESWL treatment were lower age ( p < 0.001), smaller stone size and volume (both p = 0.001). SSD, stone attenuation, sex, laterality and drainage did not have an effect on SFR in this study. After the first ESWL treatment session, 46.7% of the patients were stone-free. Conclusion: Results indicate that stone size and age are the most predictive factors for ESWL outcome. Based on this, we present a simple model for prediction of SFR after ESWL, to be used when counseling patients before ESWL treatment.